2003
DOI: 10.1038/ni881
|View full text |Cite
|
Sign up to set email alerts
|

Impaired thymic development in mouse embryos deficient in apoptotic DNA degradation

Abstract: Apoptosis is often accompanied by the degradation of chromosomal DNA. Caspase-activated DNase (CAD) is an endonuclease that is activated in dying cells, whereas DNase II is present in the lysosomes of macrophages. Here, we show that CAD(-/-) thymocytes did not undergo apoptotic DNA degradation. But, when apoptotic cells were phagocytosed by macrophages, their DNA was degraded by DNase II. The thymus of DNase II(-/-)CAD(-/-) embryos contained many foci carrying undigested DNA and the cellularity was severely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
210
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 211 publications
(218 citation statements)
references
References 50 publications
7
210
1
Order By: Relevance
“…1D). We also found that T cell blasts lacking caspase-activated DNase, which is an essential molecule for DNA fragmentation process (18), failed to undergo apoptosis even in the presence of LL-Z1640-2 (Fig. 2F).…”
Section: Blockade Of the Tak1 Signal Induces Apoptosis In Activated Tmentioning
confidence: 76%
“…1D). We also found that T cell blasts lacking caspase-activated DNase, which is an essential molecule for DNA fragmentation process (18), failed to undergo apoptosis even in the presence of LL-Z1640-2 (Fig. 2F).…”
Section: Blockade Of the Tak1 Signal Induces Apoptosis In Activated Tmentioning
confidence: 76%
“…17 Among the candidates for nucleosomal DNA fragmentation, the role of CAD/DFF40 has been well documented in many apoptotic cases both in vivo and in vitro. [18][19][20] However, it remains controversial whether the apoptotic DNase is always the same or differs depending on cell types, differentiation state, and/or apoptotic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…DNase II degrades DNA of apoptotic cells in lysosomes after phagocytes engulf them 16 . To examine the role of Tim4 in the engulfment of apoptotic cells, a fibroblast cell line expressing Tim4 was established with NIH3T3 expressing DNase II 10 (NIH3T3/DNase II/Tim4) ( Supplementary Fig.…”
mentioning
confidence: 99%